Study of feed consumptin and some of the productive traits for ration of fattening awassi lambs supplemented with pure allicin. - Lazim, Jamil Sarhan; Al-Mamore, Thaier Abed Ali Minhl (Journal of Kerbala for Agricultural Sciences, 2016)
A total number of 20 Awassi lambs of 6 – 7 months age with an initial weight of 29.8 kg were used in the experiment. lambs were randomly allocated into 4 treatments , 5 lambs for each treatment . Individual feeding was applied by offering concentrate pellets (3% of the live weight ) which supplemented with pure allicin (0 , 3 , 6 and 9 kg / ton feed ) as well as chopped alfalfa hay which was offered ad libitum along the period of the experiment which was lasted 84 days . Results revealed no significant similarities among the four treatments in feed consumption of roughage and concentrate as well as general mean of consumption which were 0.263 and 0.990 kg day for each lamb respectively .Mean while there were significant differences ( p< 0.05 ) by surpassing the second treatment in the final body weight(50.700 kg) and the total and daily gains which were 21.100 and 0.251 kg respectively as compared with the control group being , in addition it was noticed that the best feed efficiency was numerical in the 2nd and the 4th treatment as compared with the 1st and 3rd treatments ,The second treatment had exhibited higher (p≤ 0.05) final body weight (59.700 kg) and the total and daily gain.